Pakistani Early Childhood Education Classroom Quality in Terms of Structural and Procedural Aspects - Muhammad Hamza Zaheer; hassan, Dr. Khawaja Hisham ul Hassan (JECCE, 2025)
Classroom environment is a vital factor in early childhood education, serving as a key determinant of success. Organizational structure and the quality of processes together create conditions that lead to desired outcomes. This study aimed to examine classroom structural features in early childhood education within government and private schools in major cities of Punjab. Focus areas included classroom size, physical environment, academic quality, and teacher-child ratio. It also explored differences among population groups in fulfilling structural quality aspects, considering teacher self-efficacy and depressive behaviour. The research adopted a causal-comparative design. For quantitative data, 110 public and 110 private schools in Punjab were selected through ease of access. A survey method using a self-developed questionnaire was employed to collect data. The analysis was carried out with the Statistical Package for Social Sciences (SPSS) version 25.0, applying descriptive analysis. Statistical tools such as frequency analysis, independent samples t-test, and ANOVA were used to classify and interpret quantitative information. These methods allowed comparison of structural and process features of classroom quality across school types. The findings are expected to highlight differences between public and private settings, offering insights to improve classroom environments in early childhood education.